UTILIZATION OF VARIOUS TYPE OF LEARNING MEDIA TO ENGAGE STUDENTS’ LEARNING INTEREST IN EDUCATION DEPARTMENT - Aldya, Riantina Fitra; Arifendi, Rio Febrianto; Pantiwati, Yuni; Chamisijatin, Lise (Universitas Tribhuwana Tunggadewi, 2024)
This study aims to determine the student’s perceptions about utilization of various type of learning media to engage students’ learning interest. Data collection using a survey with a population of all Mathematics Education and Biology Education students of the 2022 and 2023 intakes, with a sample size of 60 students using stratified random sampling. This survey is related to perceptions related to students learning interest based on based on various of media and students learning interest from Mitchel (1993), consists of 15 items with 5 aspects such as attention, curiosity, excitement, meaningfulness, and involvement. The results showed that mostly students choose games media and games application, with 25 students (41,6%) gave highest score, mean that games media gave those students more attention because of the attraction in it, while another learning media that showed less of interest, were picture with 2 students (3,3%), power point with 6 students (10%), and learning torso with 8 students (13,3%), because visual media not fully explaining the complex material.Another survey about learning interest showed that excitement aspect, game applications gave the highest score, which was 36.6%, chosen by 22 students, followed by game media chosen by 20 students (33.3%). In the meaningfulness and involvement aspects, the learning module gave the highest score, which was 13.3% (8 students) and 35% (21 students), this is because the learning module accommodates students' independent learning so that learning becomes more meaningful. So learning modules and games based media mostly can engage students’ learning interest in education department.